A COMPARATIVE STUDY OF TRANSDERMAL BUPRENORPHINE PATCH VERSUS TRANSDERMAL DICLOFENAC PATCH FOR POST-OPERATIVE ANALGESIA IN ELECTIVE BELOW UMBILICAL SURGERIES - RAJASAB, FARHA DEEBA; CHERIAN, SHERLEY.S; KALAPPA, RAKESH; RAMACHANDRAN, HARIPRIYA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Effective postoperative pain management is crucial for recovery and patient satisfaction. This study compares the efficacy and safety of transdermal buprenorphine, an opioid analgesic, with diclofenac, a non-steroidal anti-inflammatory drug (NSAID), for postoperative pain relief in elective below umbilical surgeries. Methods: Hundred patients undergoing elective below-umbilical surgeries were randomized into two groups to receive either a transdermal buprenorphine patch or a diclofenac patch. Pain scores using the Numeric Rating Scale (NRS), functional recovery assessed by the WOMAC Index, and patient satisfaction were measured at baseline, 1 w, 2 w, and 4 w post-application. Results: Both groups showed significant pain reduction over time. However, at 1 and 2 W post-application, the diclofenac group exhibited greater pain relief (p<0.001) and higher patient satisfaction. By the 4 w, differences in pain scores and WOMAC Index between the groups were not statistically significant, indicating similar long-term efficacy. Conclusion: While both transdermal buprenorphine and diclofenac patches are effective for postoperative pain management, diclofenac patches offer superior short-term relief and patient satisfaction. Tailoring pain management strategies to individual patient needs and recovery phases is essential for optimizing postoperative care.